Community versus hospital-acquired pneumonia in patients requiring extracorporeal membrane oxygenation. (January 2019) - Park, Chul; Na, Soo Jin; Chung, Chi Ryang; Cho, Yang Hyun; Suh, Gee Young; Jeon, Kyeongman
Background: Bacterial pneumonia is a major cause of acute respiratory distress syndrome (ARDS) requiring extracorporeal membrane oxygenation (ECMO) support. However, it is unknown whether the type of pneumonia, community-acquired pneumonia (CAP) versus hospital-acquired pneumonia (HAP), should be considered when predicting outcomes for ARDS patients treated with ECMO. Methods: We divided a sample of adult patients receiving ECMO for acute respiratory distress syndrome caused by bacterial pneumonia between January 2012 and December 2016 into CAP ( n  = 21) and HAP ( n  = 35) groups and compared clinical and bacteriological characteristics and outcomes. Results: The median acute physiology and chronic health evaluation II and sequential organ failure assessment scores were 22 and 8, respectively, in the CAP and HAP groups. The most commonly identified organism in the CAP group was Streptococcus pneumonia ( n  = 12, 57.1%), while Acinectobacter baumanii was the most commonly identified in the HAP group ( n  = 13, 37.1%). However, the incidence of multidrug resistant bacteria was not different between groups (57.1% versus 74.3%, p  = 0.125). Of the 56 patients in the study, 26 were successfully weaned from ECMO, and 20 were discharged from the hospital. There were no significant differences in ECMO weaning rate (47.6% versus 45.7%, p  > 0.999) or survival to discharge rate (33.3% versus 37.1%, p  > 0.999) between the two groups. The 30-day and 90-day mortality rates were also similar. Conclusion: Patients with CAP and HAP who received ECMO for respiratory support had similar characteristics and clinical outcomes.